1976
DOI: 10.1090/s0002-9947-1976-0420572-1
|View full text |Cite
|
Sign up to set email alerts
|

Indecomposable homogeneous plane continua are hereditarily indecomposable

Abstract: ABSTRACT. F. Burton Jones [7] proved that every decomposable homogeneous plane continuum is either a simple closed curve or a circle of homogeneous nonseparating plane continua. Recently the author [5] showed that no subcontinuum of an indecomposable homogeneous plane continuum is hereditarily decomposable. It follows from these results that every homogeneous plane continuum that has a hereditarily decomposable subcontinuum is a simple closed curve. In this paper we prove that no subcontinuum of an indecompos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In § 2, we state the general (relative) version of the theory and indicate how a result of Hagopian [6] may be viewed as a consequence of it.…”
Section: James T Rogers Jrmentioning
confidence: 99%
“…In § 2, we state the general (relative) version of the theory and indicate how a result of Hagopian [6] may be viewed as a consequence of it.…”
Section: James T Rogers Jrmentioning
confidence: 99%
“…Let 6, be the chain in 5" that goes from x, to x2. Since 5" is a tree chain, (10) each link of 6, intersect 7.…”
Section: Definitions and Related Results A Space Is Homogeneous If Fmentioning
confidence: 99%
“…A continuum is hereditarily decomposable (hereditarily indecomposable) if every non-degenerate subcontinuum is decomposable (indecomposable, respectively). Hagopian [11] showed that the answer to the question of Knaster and Kuratowski is still yes if the continuum merely contains a hereditarily decomposable subcontinuum. Problème 2 by Knaster and Kuratowski was formally solved by Bing [2] who showed in 1948 that the pseudo-arc, described in detail in Section 1.1, is another homogeneous plane continuum.…”
Section: Introductionmentioning
confidence: 99%